Poly(o-phenylenediamine) colloid-quenched fluorescent oligonucleotide as a probe for fluorescence-enhanced nucleic acid detection - Tian, Jingqi (Langmuir : the ACS journal of surfaces and colloids, 2011)
In this Letter, we demonstrate that chemical oxidation polymerization of o-phenylenediamine (OPD) by potassium bichromate at room temperature results in the formation of submicrometer-scale poly(o-phenylenediamine) (POPD) colloids. Such colloids can absorb and quench dye-labeled single-stranded DNA (ssDNA) very effectively. In the presence of a target, a hybridization event occurs, which produces a double-stranded DNA (dsDNA) that detaches from the POPD surface, leading to recovery of dye fluorescence. With the use of an oligonucleotide (OND) sequence associated with human immunodeficiency virus (HIV) as a model system, we demonstrate the proof of concept that POPD colloid-quenched fluorescent OND can be used as a probe for fluorescence-enhanced nucleic acid detection with selectivity down to single-base mismatch